Prognostic factors of patients with intravascular large B cell lymphoma: a multicenter study in China - Guo, Yan; Zhong, Yi; Zhu, Lixia; Zhou, Fengping; Lin, Xuanru; Li, Xian; Wang, Xiufeng; Huang, Yan; Wu, Sun; Lv, Guoqing; Zhang, Jinghang; Zhao, Yi; et al. (Frontiers in Oncology, 2025)
Intravascular large B-cell lymphoma (IVLBCL) is a rare and highly aggressive lymphoma, but current knowledge is still inadequate. We retrospectively analyzed 50 IVLBCL patients from five Chinese tertiary hospitals in China between 2017 and 2024. Hemophagocytic variant (HV) patients showed worse performance status, universal B symptoms, more bone marrow infiltration, higher mortality, pancytopenia, elevated inflammatory markers (CRP, LDH, ferritin), hypoglobulinemia and hypogammaglobulinemia. Among 46 treated patients, CR/CRu rate was 71% (27/38). The 2-year OS was 65.5%, significantly worse in HV vs. classical variant (CV) (43.3% vs. 76.4%, P = 0.007). Multivariate analysis identified CNS involvement (HR = 10.86, P < 0.001), HV subtype (HR = 1.91, P = 0.018), and nodal organs involvement (HR = 5.26, P = 0.052) as poor prognostic factors. IVLBCL exhibits marked heterogeneity, with HV and CNS involvement conferring dismal outcomes. This study provides key diagnostic/therapeutic insights for IVLBCL in China, warranting prospective trials to validate prognostic models and optimize therapies.